Stainless steel foam as wick material in heat pipe for electronics cooling application. Issue 1 (1st February 2022) - Ginting, Fitri H S; Humaidi, Syahrul; Tetuko, Anggito P
Abstract: In this preliminary investigation, we analyzed the possibility using a stainless steel foam as a wick material in heat pipe. The heat pipe will be used as a passive cooling sytem in electronic devices. Stainless steel foam that used in the current investigation is a commercial foam that has been treated to be characterized using SEM and 3D optical microscope. Analytical models were also developed to calculate the capillary pressure and effective thermal conductivity of the stainless steel foam. The analytical model revealed that the optimum stainless steel foam to be used as wick material is found at the pore size, porosity and contact angle of 30 μm, 0.1 and 0°, respectively.